2006
DOI: 10.1080/17450390500468487
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the biotin flow at the duodenum of dairy cows fed diets with different concentrate levels and types of forages

Abstract: Biotin is involved in many vital metabolic pathways and must be provided for an efficient fermentation in the rumen, as well as for the intermediary metabolism of the host animal. Factors influencing ruminal biotin metabolism and output are widely unknown at present. Therefore, dairy cows fitted with permanent cannulas in the dorsal rumen and in the proximal duodenum were fed differently composed diets, and the biotin flow at the proximal duodenum was measured. The diets (on DM basis) consisted of 8.9 kg grass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Cruyvagen and Bunge (18) observed higher fermentability and NDF digestibility of roughages in in vitro studies conducted using rumen liquor from cows that were supplemented with 40 mg of biotin for 21 days (equivalent to 2.67 mg/kg DMI). Lebzien et al (19) reported that the amount of biotin available in the duodenum of cattle was not dependent on the diet composition or oral biotin supplementation, but on the total RMBP synthesis and fermented OM. In the present study, the effect of different doses of biotin ranging from 0.323 to 1.615 mg/ kg DMI was tested.…”
Section: Discussionmentioning
confidence: 99%
“…Cruyvagen and Bunge (18) observed higher fermentability and NDF digestibility of roughages in in vitro studies conducted using rumen liquor from cows that were supplemented with 40 mg of biotin for 21 days (equivalent to 2.67 mg/kg DMI). Lebzien et al (19) reported that the amount of biotin available in the duodenum of cattle was not dependent on the diet composition or oral biotin supplementation, but on the total RMBP synthesis and fermented OM. In the present study, the effect of different doses of biotin ranging from 0.323 to 1.615 mg/ kg DMI was tested.…”
Section: Discussionmentioning
confidence: 99%